Factors Affected Low Coverage of Exclusive Breast Feeding in Cilacap Tengah, Central Java, Indonesia - Pemi Sunarsih Ruhyana; Pawito -; Uki Retno Budhiastuti (Journal of Health Policy and Management, 2016)
Background: Human resources (HR) quality is a requirement of absolute attainment of development in all fields. Nutritional status of being one of the very important factors in the quality of human resources is mainly associated with intelligence, productivity and creativity. To achieve an optimum between flower growing by giving breast milk to infants from birth in the early minutes of life until the age of 6 months exclusive breast milk given without other food. This study was aimed to determine the cause of the low coverage of breast milk exclusively and the factors that affected it.Subject and methods: This was a case study with qualitative design, was carried out in July-August 2016 in Cilacap, Central Java. A total sample of parents with infants aged 7-24 months of age, the mother/mother-in-law and health workers. The data was collected by interviews, observation and documents, and analyzed with data presentation, data reduction, and the withdrawl of the conclusion.Results: Pre-disposing Factors good motivation, attitudes, education and employment of the informant was indeed affect Exclusive breast feeding in the process. Enabling Factors are readily available and easily accessible due to the support of the party giver services though in terms of infrastructure there are still shortcomings in various things. While Reinforcing factors demonstrates the role of health workers and the people closest to either mother or mother-in-law strongly affect the behavior ofthe mother in giving breast feedingexclusively. Restricting factors namely wrong beliefs about the incessant promotion of baby food, infant formula and health problems in the mother and the baby. In addition, the existence of the recording and reporting of less fit so that it affects the actual coverage figures in society.Conclusion: the cause of the low coverage of exclusive breast feeding include knowledge of mother/mother-in-law limited about breast milk exclusively, the role of health workers that is not optimal, the existence of a mistaken beliefs and culture in the community about BREAST MILK exclusively and recording and reporting factors that still need to be addressed so that Exclusive breast feeding data in accordance with the conditions in the community.Keywords: exclusive breast feeding, coverageCorrespondence: Pemi Sunarsih Ruhyana. Midwifery Academic Graha Mandiri Cilacap, Jl. Dr. Soetomo No. 4B Cilacap. Email: pemisunarsihruhyana@gmail.com.Journal of Health Policy and Management (2016), 1(1): 20-28https://doi.org/10.26911/thejhpm.2016.01.01.04